Emerging applications of femtosecond laser fabrication in neurobiological research - Tian, Mingzhen; Ma, Zhuo-Chen; Han, Qingqing; Suo, Qian; Zhang, Zhijun; Han, Bing (Frontiers in Chemistry, 2022)
As a typical micro/nano processing technique, femtosecond laser fabrication provides the opportunity to achieve delicate microstructures. The outstanding advantages, including nanoscale feature size and 3D architecting, can bridge the gap between the complexity of the central nervous system in virto and in vivo. Up to now, various types of microstructures made by femtosecond laser are widely used in the field of neurobiological research. In this mini review, we present the recent advancement of femtosecond laser fabrication and its emerging applications in neurobiology. Typical structures are sorted out from nano, submicron to micron scale, including nanoparticles, micro/nano-actuators, and 3D scaffolds. Then, several functional units applied in neurobiological fields are summarized, such as central nervous system drug carriers, micro/nano robots and cell/tissue scaffolds. Finally, the current challenges and future perspective of integrated neurobiology research platform are discussed.